PENGARUH FRAUD PENTAGON TERHADAP TINGKAT KECURANGAN LAPORAN KEUANGAN (PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2019) - Melani, Leni Machfatul; Sudibyo, Tyagita Dianingtyas (IJMA (Indonesian Journal of Management and Accounting), 2020)
This research aims to analyze the effect of pressure, opportunity, rationalization, competence, and arrogance on the level of financial statement fraud in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019 period. The data used in this study are secondary data obtained from financial statements and annual reports of food and beverage companies listed on the Indonesia Stock Exchange for the 2019 period. The sampling technique in this study used purposive sampling to obtain 17 food and beverage companies for the 2019 period. The data analysis techniques used were descriptive analysis and multiple linear regression analysis using SPSS 22 software. The results of this study indicate that pressure, opportunity, rationalization, competence does not have a significant effect while arrogance has a significant effect on the level of fraud in a financial statement on food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019 period.